Development and study of a microprocessor automatic control system for a mono-switch tie type with a linear inductive electric motor and a discrete speed controller - Buriakovskyi, S. G.; Asmolova, L. V.; Maslii, An. S.; Maslii, Ar. S.; Obruch, I. V. (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article is devoted to the development of the microprocessor automatic control system for a gearless controlled electric drive of a mono-switch tie based on a linear inductor electric motor. This solution provides control the position of the switch point, to carry out the transfer process with a smooth drive of shanks to the frame rail, to protect electric motor elements from overloads. Goal. Development and study of the behavior of microprocessor automatic control system for mono-switch tie type with linear inductive electric motor and discrete PID speed controller which coefficients are adjusted according to Chien-Hrones-Reswick method to meet modern traffic safety requirements and improve operational reliability factors. Methodology. On the basis of electric drive theory, a kinematic line of a mono-switch tie type with nonlinear friction characteristic is presented. Using differential equation theory and Laplace transformation, a mathematic description of a linear inductor electric motor has been made. Using the z-transform method, a difference equation for describing a discrete PID speed controller is obtained, the coefficients of which are derived using the Chien-Hrones-Reswick method. A simulation mathematical model of the electric drive mono-switch tie type as the microprocessor automatic control system with linear inductive electric motor and discrete PID speed controller and nonlinear friction characteristic was built in MATLAB. Results. Simulation modelling of a mathematical model of the microprocessor automatic control system of the electric drive mono-switch tie type with the linear inductive electric motor and discrete PID speed controller and nonlinear friction characteristic have been developed and performed. Studies of dynamics of switch point movement have shown that, a drive time of less than 0.7 s at a constant speed motor armature of 0.2 and 0.3 m/s provides to meet modern requirements for railway switch points. The application of discrete PID speed controller has shown improved dynamics of switch point. Originality. First for the electric drive of the mono-switch tie type with linear inductive electric motor a mathematical model of the discrete PID speed controller and nonlinear friction characteristic as an object of speed control of switch point movement, has been developed. Practical value. Mathematical model of a railway track switch of the mono-switch tie type with linear inductive electric motor and discrete PID speed controller has been developed to carry out the control of the position of the switch point, process with a smooth drive them to the frame rail, to protect electric motor elements from overloads.

Робота присвячена розробці мікропроцесорної системи автоматичного керування безредукторним регульованим електроприводом стрілочного переводу моношпального типу на базі лінійного індукторного двигуна. Таке рішення дозволяє контролювати положення гостряків, здійснювати процес переводу з плавним доводом гостряків до рамної рейки, захистити елементи електродвигуна від перевантажень. Запропоновано структурну схему дискретного ПІД-регулятора швидкості, синтезованого в z-зображенні та отримано діаграми розподілу його коефіцієнтів за методом Чина-Хронса-Ресвіка. Наведені результати комп’ютерного моделювання показали, що час переводу гостряків менший ніж 0,7 с при сталому рівні задавання швидкості якоря 0,2 і 0,3 м/с, що дозволяє реалізувати сучасні вимоги до стрілочних переводів залізничного транспорту.
Розробка та дослідження мікропроцесорної системи автоматичного керування моношпального стрілочного переводу з лінійним двигуном індукторного типу та дискретним регулятором швидкості
Keywords: electric drive with linear inductive electric motor; electromechanical system; control system; discrete PID speed controller; електропривод з лінійним індукторним двигуном; електромеханічна система; система керування; дискретний ПІД-регулятор швидкості